Level of satisfaction of the Philippine National Police uniformed personnel, retirees and beneficiaries on the delivery of service by the finance unit of the Ilocos Norte Police Provincial Office - Espejo, Roy Paranada, Jr. (Laoag City : [s.n.], 2017)
This study determined the level of satisfaction of the Philippine National Police (PNP) uniformed personnel, retirees, and beneficiaries on the services provided by the Finance Unit of the Ilococ Norte Police Provincial Office (INPPO). This study followed the descriptive correlational research design using documentary analysis and questionnaires to gather data from the PNP uniformed personnel, retirees, and beneficiaries who recieved and/or availed the benefits of the police organization through the Finance Unit of the INNPO for 2016. Frequency, rank, weighted mean, and Pearson r of correlation were used to analyze and interpret the data gathered.
Bibliography: pages 98-101.
CHED-La Union
Keywords: Police